ANALISIS COMMUNITY BASED TOURISM (CBT) DALAM MENDUKUNG PARIWISATA BERKELANJUTAN DI AGRO EDUWISATA ORGANIK MULYAHARJA, KOTA BOGOR - Sherlina; Prayogo Susanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of Community Based Tourism (CBT) in supporting sustainable tourism at Agro Edukasi Wisata (Agroeduwisata) Organik Mulyaharja, Bogor City. This research uses a descriptive qualitative approach with data collection techniques including interviews, observations, and documentation. The informants consist of managers, local communities, business actors, and visitors as supporting data. Data analysis was conducted through data reduction, data presentation, and conclusion drawing and verification, supported by SWOT analysis. The results show that the implementation of Community Based Tourism (CBT) in Agro Eduwisata Organik Mulyaharja has been carried out quite well. In the economic dimension, tourism activities have created job opportunities and business prospects for the local community, although income still depends on the harvest season. In the social dimension, community involvement is relatively high and contributes to improving the quality of life and community pride. In the cultural dimension, tourism activities support the preservation of local culture. In the environmental dimension, efforts to manage the environment have been implemented; however, there are still issues related to increased waste during tourism activities. Meanwhile, in the political dimension, the community has been involved in tourism activities, but has not yet achieved full independence in management. From the perspective of sustainable tourism, Agro Eduwisata Organik Mulyaharja has contributed positively to socio-cultural and economic aspects. However, improvements are still needed in environmental management and accountability to achieve optimal sustainability.